Molecular ferroelectric self-assembled interlayer for efficient perovskite solar cells - Chang Xu; Pengjie Hang; Chenxia Kan; Xiangwei Guo; Xianjiang Song; Chenran Xu; Guofeng You; Wei-Qiang Liao; Haiming Zhu; Dawei Wang; Qi Chen; Zijian Hong; et al. (Nature Communications)
Abstract The interfacial molecular dipole enhances the photovoltaic performance of perovskite solar cells (PSCs) by facilitating improved charge extraction. However, conventional self-assembled monolayers (SAMs) face challenges like inadequate interface coverage and weak dipole interactions. Herein, we develop a strategy using a self-assembled ferroelectric layer to modify the interfacial properties of PSCs. Specifically, we employ 1-adamantanamine hydroiodide (ADAI) to establish robust chemical interactions and create a dipole layer over the perovskite. The oriented molecular packing and spontaneous polarity of ferroelectric ADAI generate a substantial interfacial dipole, adjusting band bending at the anode, reducing band misalignment, and suppressing charge recombination. Consequently, our formamidinium lead iodide-based conventional PSC achieves efficiencies of 25.13% (0.06 cm2) and 23.5% (1.00 cm2) while exhibiting enhanced stability. Notably, we demonstrate an impressive efficiency of 25.59% (certified at 25.36%) in a 0.06 cm2 area for the inverted champion device, showcasing the promise of ferroelectric SAMs for PSCs performance enhancement.